2018
DOI: 10.1002/jip.1505
|View full text |Cite
|
Sign up to set email alerts
|

The mental nose and the Pinocchio effect: Thermography, planning, anxiety, and lies

Abstract: We applied thermography to cognitive neuropsychology, particularly as a somatic marker of subjective experience during cognitive and emotional tasks. We found significant correlations between changes in facial temperature and mental set. Specifically, the temperature of the nose tended to decrease during emotional tasks and increase during cognitive tasks. However, for stress tests or high arousal reactions to emotional stimuli, the direction of the thermal change depended on the nature of the setting, real or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
4
2
0
1
Order By: Relevance
“…Although no interaction effects for most ROI temperature slopes were found, a strong, statistically significant effect of the interaction between condition and emotion when evaluating the temperature slope on the nose tip was observed. This result confirms again the assumption that the nasal area is a salient region for emotion detection [32,67,[92][93][94][95]. Recent studies included applications with more challenging populations such as infants and children.…”
Section: Thermal Ir Imaging-based Affective Computing In Hrisupporting
confidence: 81%
“…Although no interaction effects for most ROI temperature slopes were found, a strong, statistically significant effect of the interaction between condition and emotion when evaluating the temperature slope on the nose tip was observed. This result confirms again the assumption that the nasal area is a salient region for emotion detection [32,67,[92][93][94][95]. Recent studies included applications with more challenging populations such as infants and children.…”
Section: Thermal Ir Imaging-based Affective Computing In Hrisupporting
confidence: 81%
“…A positive correlation was also observed after the simulation practice in undergraduate students. These results confirmed that higher anxiety levels may be associated with the increase in the forehead temperature, as suggested by previous works [ 29 , 30 , 31 , 32 ]. Since the forehead area is one of the most stable temperature regions due to central vessel irrigation, thermal variations in this area are of great importance to provide information about stress diagnosis [ 30 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Particularly, greater thermal variations have been reported in the nose temperature under stressful conditions in comparison with the cheekbone and the forehead [ 21 ]. A similar behavior was observed in our study when comparing temperature variations before and after simulation [ 29 ]. Likewise, higher thermal gradients were found in postgraduate students due to higher differences in stress and anxiety levels between pre-test and post-test measurements.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations